PENGARUH PROBLEM BASED LEARNING TERHADAP KEMANDIRIAN BELAJAR KOMPUTER AKUNTANSI MAHASISWA PENDIDIKAN EKONOMI AKUNTANSI - Fahrina, Sri; Johan, Rina Selva; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effect of Problem Based Learning to Autonomy Learning computer accounting student Accounting Economics Education University of Riau . This research was conducted at the University of Economics Education Riau.Populasi of this study is education students 2013-2014 economic forces numbering 38 people . Samples taken by jenuh.Teknik sample method of data analysis used is simple linear regression . The results of this study indicate that : Learning model Learning Problem baesd affect the Kemanndirian Learning computer accounting student Accounting Economics Education . Keywords : Problem Based Learning , Learning Independence